BOAZ HAGIN’S PHILOSOPHY OF DEATH AS REFLECTED IN THE HUNGER GAMES TRILOGY FILMS - Hidayatul Nurjanah (Universitas Gadjah Mada, 2021)
The Hunger Games is one of Hollywood films that contains deaths and deadly scenes throughout its trilogy. There are plenteous meanings of deaths that can be analyzed from the films, which will develop new meanings and definitions of deaths as an interesting topic to discuss. The researcher employed Boaz Hagin's framework of death because Hagin provides a framework about deaths and how deaths can be meaningful. In his book, he writes a broader range of philosophical description about deaths in Classical Hollywood Cinema which explores the morality and ethical values of mainstream films that portrays death as a meaningful part of life. The research problem is what is the meaning of deaths found in Hunger Games using Hagin’s framework of deaths. This research was conducted using a descriptive qualitative approach aiming at describing the phenomenon and characteristics. The data collected qualitatively by examining them throughout to get relevant issues and ideas and classify them. The findings show that death can bring meanings to characters in the films, such as a death in line where death means as a savior for their beloved ones, death as politic seen from the characters' past life that brings hope for the future, death as the Access, Authority, and Test, can be seen from how the characters use their talent to survive.